Zur Verteilung der Werte von multiplikativen zahlentheoretischen Funktionen - Juškys, Z. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:З. Юшкис. К вопросу о распределении значений арифметических мультипликативных функцийZ. Juškys. Apie multiplikatyvinių aritmetinių funkcijų pasiskirstymą